Integrasi Nilai-Nilai Karakter Mohammad Hatta pada Pembelajaran Sejarah Sebagai Penguatan Karakter Siswa SMA - Mindarto, Mindarto; Marta, Nuraeni; Abrar, Abrar (Jurnal Paedagogy, 2023)
This research aims to examine Mohammad Hatta’s character values in history lessons so that these values can be integrated into history lessons to strengthen the character of high school students. The method used in this research was a descriptive method with an ethnographic approach. Data collection techniques used observation, interviews, and documentation which were analyzed descriptively. Triangulation techniques were used to investigate the data’s interpretative significance. According to the study findings, Mohammad Hatta’s character values that can be applied and integrated into learning are book lover, discipline, honesty, and simplicity. Students can emulate Mohammad Hatta’s character and apply it in the classroom and everyday life by being diligent in reading (book lovers), obeying rules, and being on time (discipline). Furthermore, it is done by answering exam questions alone without cheating, accepting something when it becomes right (honest), and not wearing excessive accessories (simple).